PENGARUH LINGKUNGAN KERJA DAN PROMOSI JABATAN TERHADAP STRESS KERJA KARYAWAN PT. HIMAWAN PUTRA MEDAN. - Ivany Ivany; Syawaluddin Syawaluddin; Aidil Putra (JURNAL BISNIS KOLEGA, 2022)
In creating a strong and successful company, a supportive work environment is needed and clear promotions are needed so that employees do not stress in carrying out work activities in the company. The purpose of this study was to determine the effect of the work environment and job promotions on Employee Stress at PT. Himawan Putra Medan.The research method used is a quantitative analysis method. The data used are primary andÂ secondary data. The study population was 50 people using saturated sampling techniques where all members of the population were sampled. Variables are measured with a Likert scale. The data analysis technique used is multiple linear regression.Based on simultaneous analysis of the work environment and job promotions affect the Employee Stress of PT. Himawan Putra Medan. Partially, there is an influence of work environment variables on employee work stress and there is an influence of job promotion on PT. Himawan Putra Medan. Â Keywords: Work Environment, Job Promotion, Employee Stress